Ego Depletion in Real-Time: An Examination of the Sequential-Task Paradigm - Arber, Madeleine M.; Ireland, Michael J.; Feger, Roy; Marrington, Jessica; Tehan, Joshua; Tehan, Gerald (Frontiers in Psychology, 2017)
Current research into self-control that is based on the sequential task methodology is currently at an impasse. The sequential task methodology involves completing a task that is designed to tax self-control resources which in turn has carry-over effects on a second, unrelated task. The current impasse is in large part due to the lack of empirical research that tests explicit assumptions regarding the initial task. Five studies test one key, untested assumption underpinning strength (finite resource) models of self-regulation: Performance will decline over time on a task that depletes self-regulatory resources. In the aftermath of high profile replication failures using a popular letter-crossing task and subsequent criticisms of that task, the current studies examined whether depletion effects would occur in real time using letter-crossing tasks that did not invoke habit-forming and breaking, and whether these effects were moderated by administration type (paper and pencil versus computer administration). Sample makeup and sizes as well as response formats were also varied across the studies. The five studies yielded a clear and consistent pattern of increasing performance deficits (errors) as a function of time spent on task with generally large effects and in the fifth study the strength of negative transfer effects to a working memory task were related to individual differences in depletion. These results demonstrate that some form of depletion is occurring on letter-crossing tasks though whether an internal regulatory resource reservoir or some other factor is changing across time remains an important question for future research.